The Manifestation of Human Greed in Ursula K. Le Guin’s ‘Those Who Walk Away from Omelas’ - Abdelrahman Jalal Othman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
With the rise of capitalism as the dominant system of economy and investment in the late twentieth century and with the use of all the different means to achieve the American Dream, humanity has been confronted with an unprecedented level of avarice and greed. The vast majority of the populations in different parts of the world were victimized as a result of the limitless level of possessional lust and greed of the few. Ursula K. Le Guin’s The Ones Who Walk Away from Omelas is a clever manifestation of this unfavorable condition. This research paper aims at highlighting the different means used by the author to question the readers’ ethical basis of accepting to base one’s happiness on the misery of others. The researcher indicates that the motivating force behind accepting such a bargain is uncontrolled greed. While the paper criticizes the prevailing norm of excessive material gain at whatever cost practiced by many people in the world; it also shows that only very few people are ready to take any effective action to put any limit to this inhumane phenomenon. Finally, even though the novel is depicting a gloomy view of the modern world, yet there is a glimpse of hope that the few good people can resist the status quo and refuse to live happily while the price is paid by innocent people.